Optimization of Procurement Processes in Wooden-Packaging s.r.o. - Králík, Pavel; Vinš, Marek; Jirsák, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This master’s thesis focuses on the optimization of procurement processes within a small to mid-size manufacturing company that has experienced significant growth in recent years. The objective is to improve and rescale the original procurement system to align with the bigger size and scope of the company today. The theoretical part presents frameworks and concepts that are crucial for analyzing and improving procurement processes and inventory management, such as ABC Analysis, XYZ Analysis, and the Kraljic Matrix. The practical part begins with a comprehensive description of the company’s original procurement system, summarizing the challenges and problems faced, including findings gathered from interviews with executives. Subsequent parts provide an in-depth review of all conducted analyses, proposed solutions, and a detailed description of the solutions implemented. The implementations from this thesis have successfully reduced the capital tied up in inventory, and additional annual savings are expected, mainly due to a more effective tendering method that has resulted in lower purchasing prices, alongside enhanced quality control.
Vedoucí práce: Marek Vinš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses